Black South Africans’ Perceptions of Psychotherapy and Counselling - Daniel Letsoalo; Slindokuhle Mathebula (Kuras Institute, 2026)
The public health issue of mental health is a concern in South Africa. However, studies indicate that only a minority of Black South Africans pursue psychotherapy and/or counselling, while most, around eighty percent, rely on traditional healers for mental health issues, unlike their white counterparts. This qualitative study, grounded in social constructivism and phenomenological design, examined the perceptions of psychotherapy and/or counselling among Black South Africans in the Soweto township of Gauteng Province, South Africa. It aimed to understand this conundrum and discrepancy. Data was generated through individual face-to-face semi-structured interviews and analysed through thematic analysis. The analysis uncovered different themes and sub-themes. The findings revealed that Black individuals have a reasonable understanding of psychotherapy and/or counselling. Furthermore, the study demonstrated a shift in perception among Black South Africans, as they expressed a combination of negative and positive opinions on psychotherapy and/or counselling. The results of this study emphasise the need for heightened awareness campaigns to address, clarify and demystify negative perceptions. Additionally, there is a need for targeted interventions that are relatable, relevant, context-specific, and sensitive to the needs of Black South Africans. Future studies should consider conducting a longitudinal study to monitor the trajectory of the perceptions of Black South Africans over time.